Role of Real Time Ultrasound B-Scan in Eyes with Advanced Cataract, by Documenting Frequency of Different Posterior Segment Pathologies - Asim, Urossa; Niaz, Ayesha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the role of real time ultrasound B-scan in postoperative prognosis among patients with advanced cataract by documenting preoperative frequency of different posterior segment pathologies.Study Design: Cross-sectional study.Place and Duration of Study: Radiology Department, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Oct 2011.Methodology: The study utilized ultrasound eye, carried on the patients with closed eyes in supine position with ultrasound transmission gel applied to prevent transducer touching eyelid.  Scan was performed in both sagittal and transverse plane.Results: A total of 336 patients were included in this study, with mean age of 56.92±12.89 years, 162(48.21%) male rest female. Cataracts were found in 144 (42.86%) left eyes and 154 (45.83%) right eyes. Mature cataract was seen in 292 (86.9%) patients, while 32(9.52%) had traumatic and 304(90.47%) had non-traumatic cataract. In non-traumatic cataract, retinal detachment (RD) was in 14(4.6%) patients, vitreous detachment (VD) in 13(4.3%) and vitreous detachment/hemorrhage in 21(6.9%) patients. Optic disc cupping was seen in 6(2.0%) non-traumatic cases and other pathologies were seen in 7(2.3%) patients having non-traumatic and 3(9.38%) patients having traumatic cataract.Conclusion: Preoperative posterior segment evaluation with ultrasound in patients with dense cataract can be used to detect pathologies that may influence the surgical strategy and postoperative visual prognosis.